2019
DOI: 10.2147/ott.s221354
|View full text |Cite
|
Sign up to set email alerts
|

<p>Research Progress in microRNA-Based Therapy for Gastric Cancer</p>

Abstract: Gastric cancer (GC) is one of the leading causes of tumor-related mortality. In addition to surgery and endoscopic resection, systemic therapy remains the main treatment option for GC, especially for advanced-stage disease and for cases not suitable for surgical therapy. Hence, improving the efficacy of systemic therapy is still an urgent problem to overcome. In the past decade, the essential roles of microRNAs (miRNAs) in tumor treatment have been increasingly recognized. In particular, miRNAs were recently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 163 publications
0
12
0
Order By: Relevance
“…According to the last updated European Society for Medical Oncology (ESMO) clinical practice guidelines for the treatment of cancer, 5-fluorouracil (5-FU), along with other agents, is the first line perioperative chemotherapy regimen for patients with stage I.B resectable GC [ 95 ]. Several studies have shown that miRNAs, including miR-21, might be involved in the tumor resistance mechanisms of 5-FU by decreasing the expression levels of their target genes, suggesting anti-miRNA-21 (AMO-21) therapies may play a pivotal role in cancer treatment [ 96 , 97 ]. Indeed, downregulation of miR-21 increases the sensitivity of human epidermal growth factor receptor 2 (HER2)-positive GC in response to both 5-FU and trastuzumab by upregulating target genes of miR-21, SPRY2 , and PTEN, respectively [ 98 ].…”
Section: Role Of Mir-21 As a Diagnostic Predictive And Therapeutic Biomarker Across Cancers In Digestive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the last updated European Society for Medical Oncology (ESMO) clinical practice guidelines for the treatment of cancer, 5-fluorouracil (5-FU), along with other agents, is the first line perioperative chemotherapy regimen for patients with stage I.B resectable GC [ 95 ]. Several studies have shown that miRNAs, including miR-21, might be involved in the tumor resistance mechanisms of 5-FU by decreasing the expression levels of their target genes, suggesting anti-miRNA-21 (AMO-21) therapies may play a pivotal role in cancer treatment [ 96 , 97 ]. Indeed, downregulation of miR-21 increases the sensitivity of human epidermal growth factor receptor 2 (HER2)-positive GC in response to both 5-FU and trastuzumab by upregulating target genes of miR-21, SPRY2 , and PTEN, respectively [ 98 ].…”
Section: Role Of Mir-21 As a Diagnostic Predictive And Therapeutic Biomarker Across Cancers In Digestive Systemmentioning
confidence: 99%
“…Cisplatin is another first-line chemotherapy agent that has been frequently studied. Zheng and colleagues have noted that exosomal miR-21 that is directly transferred from tumor-associated macrophages to the GC cells may confer cisplatin-resistance in GC by suppressing cell apoptosis and activating the PI3K/AKT signaling pathway, which in turn is achieved by downregulation of PTEN expression [ 96 , 97 ]. Additionally, the role of miR-21-5p in doxorubicin (DOX) and trastuzumab (a HER2-targeting monoclonal antibody) resistant GC has also been studied.…”
Section: Role Of Mir-21 As a Diagnostic Predictive And Therapeutic Biomarker Across Cancers In Digestive Systemmentioning
confidence: 99%
“…Extracellular vesicles contain receptors, bioactive lipids, proteins, and nucleic acids and play an important role in cell-to-cell communication ( 21 ). A large number of studies ( 22 , 23 ) have reported that the exosomes contain many important proteins that can be used for early tumor diagnosis or patient prognosis analysis. Hence, in this study we investigated the prognostic value of SENP1 in patients with osteosarcoma by determining the concentration of plasma exosomes from patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of studies demonstrated that long noncoding RNAs (lncRNAs) may exert critical roles in GC occurrence and development [4,5] and microRNAs (miRNAs) function as essential regulators via involvement in various signaling transduction pathways in GC progression [6]. Moreover, increasing studies have demonstrated that a number of lncRNAs function as competitive endogenous RNAs (ceRNA), by which lncRNAs can restore the repression of downstream target genes via sponging miRNAs in GC cells [4,7].…”
Section: Introductionmentioning
confidence: 99%